Australian Journal of Islamic Studies - Charles Sturt University. Centre for Islamic Studies and Civilisation (Islamic Sciences and Research Academy of Australia, 2016)
Devoted to research and scholarship in Islam and Muslims including theology, philosophy, sociology, jurisprudence, contemporary studies, comparative religion, spirituality, Qur’anic and Sunnah studies, history and art.
Keywords: Social Sciences : Periodicals; Humanities : Periodicals; Islam : 21st century : Periodicals; Sunna; Islamic art; Islam and state : Qurʼanic teaching; Australia; Australian; Islamic studies; Muslim studies